Does Clearance of Positive Margins Improve Local Control in Oral Cavity Cancer? A Meta‐analysis. (26th March 2019) - Bulbul, Mustafa G.; Tarabichi, Osama; Sethi, Rosh K.; Parikh, Anuraag S.; Varvares, Mark A.
Abstract : Objectives: To compare local recurrence‐free survival (LRFS) in early oral cavity cancer (OCC) patients with positive/close frozen section (FS) cleared with further resection (R1 to R0) or positive FS not cleared (R1) to those with negative margins on initial FS analysis (R0). Data Sources: PubMed, EMBASE, and Cochrane. Review Methods: We followed the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) for reporting in our study. Only English‐language articles that included patients with OCC and local recurrence (LR) comparisons between R0 and initially R1 to final R0 or final R1 groups were included. We requested the raw data from the corresponding authors of eligible studies and performed an individual participant data (IPD) meta‐analysis of LRFS outcomes across groups. Results: Pooled LRFS data from 8 studies showed that patients in the R1 to R0 group had worse LRFS compared to the R0 group (hazard ratio [HR] = 2.897, P <. 001). Patients in the R1 group were also found to have worse LRFS compared to the R0 group (HR = 3.795, P <. 001). When compared to final R1 group, the initially R1 to final R0 only showed a trend toward better LRFS. Conclusion: Margin revision of initially positive margins to "clear" based on FS guidance does not equate to an initially negative margin and does not significantly improve local control. These findings call into question the effectiveness of the current methodology of intraoperative FS in OCC resections and call for a prospective study to determine what system of resected specimen analysis best predicts completeness of resection.